Synthesis of 2H-1,4-Benzoxazin-3(4H)-ones via Smiles Rearrangement - Zhou, Jia-Zhou; Li, Zhu-Bo; Yang, Hao; He, Xiao-Yan; Wang, Li-Ying; Tian, Xiao; Lv, Ting-Ting; Zuo, Hua (Asian Journal of Chemistry, 2011)
An efficient synthetic route for novel 2H-1,4-benzoxazin-3(4H)-ones via smiles rearrangement is developed. Reaction of primary amine and chloroacetyl chloride gave 2-chloroacetamide, which reacted with 2-chlorophenol, followed by Smiles rearrangement to obtain a series of new 2H-1,4-benzoxazin-3(4H)-ones (yield 45-90 %).